As paixões na Suma Teológica de Tomás de Aquino - Gonzalez, José Antonio (2025)
This work explores the complex subject of the passions of the soul, a matter that has generated intense discussions and diverse opinions throughout history. The central questions addressed include: the nature of the passions, their number, their order and hierarchy, and their morality. We will study and present the exposition and solutions that Thomas Aquinas provides to these questions in his treatise on the passions in the Summa Theologica (S.Th. Ia-IIae qq.22-48). We chose this author for his ability to synthesize and cohesively organize the classical and medieval knowledge on passions, and we preferred his treatise in the Summa for being his most profound and mature work on the subject. This research concludes that for Thomas, the passions are movements of the sensitive appetite in response to the perception of something useful or harmful and involve a bodily transmutation. Regarding their number, Thomas distinguishes 11 principal passions, determined by four divisions. In terms of their order, the first is love and the last are joy and sadness. The concupiscible passions precede the irascible ones, and those directed towards good precede those directed towards evil. In relation to the morality of the passions, in themselves, as movements of the sensitive appetite, they do not possess morality, but through their relation to the intellect and the will, they can acquire moral value